Nonexistence of critical fuel moisture content for flammability - Terrah, S.M.; Sabi, F.Z.; Mosbah, O.; Dilem, A.; Hamamousse, N.; Sahila, A.; Harrouz, O.; Boutchiche, H.; Chaib, F.; Zekri, N.; Kaiss, A.; Clerc, J.-P.; et al. (Fire safety journal, 2020)
The critical moisture of ignition is still a subject of extensive studies, and an endothermic/exothermic phase transition is expected to occur near the critical region. Ignition tests were realized for live pinus halepensis needles using a cone calorimeter. By definition, phase transitions occur when a small variation of an external control parameter leads to a qualitative modification of the system. In order to determine whether the moisture content is the control parameter of the endothermic/exothermic phase transition or not, we had to verify the existence of a moisture threshold for ignition by analyzing the ignition time dependence on moisture content. The experimental data have shown no critical moisture for the fuel ignition. We pointed out that the observed critical region corresponds to an ignition critical heat flux rather than a critical moisture. Instead of a critical moisture, a characteristic moisture content is observed. Above this moisture, ignition time increases exponentially. A further discussion on the existence of a critical moisture for spread is provided. •Cone calorimeter ignition of partially (microwave) dried live fuel was realized.•The partial drying process allows the variation of moisture content.•From experimental results, there is no critical moisture content for ignition (hc=100%, i.e. only water).•Characteristic moisture for ignition was observed that is related to bound water in the fuel particles.•Critical moisture is expected for fire spread due to the finite residence time of the flames.